Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees